2019
DOI: 10.3390/antiox8120646
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Constituents of Chrysophyllum oliviforme L. Leaf Down-Regulate TGF-β Expression and Ameliorate CCl4-Induced Liver Fibrosis: Evidence from In Vivo and In Silico Studies

Abstract: The prevalence of hepatic diseases globally and in Egypt particularly necessitates an intensive search for natural hepatoprotective candidates. Despite the traditional use of Chrysophyllum oliviforme L. and C. cainito L. leaves in the treatment of certain ailments, evidence-based reports on their bioactivities are limited. In this work, in vivo and in silico studies were conducted to evaluate their methanol extracts potential to alleviate liver damage in CCl4-intoxicated rats, in addition to their antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Surprisingly, HPLC analysis with standard flavonoids such as luteolin, kaempferol, and quercetin did not show any significantly identified levels of these compounds ( Figure 1 e), implying that major principles are not related to simple flavonoid backbones, and further phytochemical studies are needed. However, chemical analysis with Chrysophyllum plants such as C. lacourtianum, C. oliviforme, C. cainito , C. albidum, and C. pruniforme have been reported [ 37 , 38 , 39 , 40 ]. A variety of compounds, including 3-galloyl myrecetrin, rutin, quercetrin, myrecetrin, myricetin, quercetin, isoquercitrin, kaempferol, caffeic acid, trans-ferulic acid, gallic acid, stigmasterol, epicatechin, epigallocatechin, procyanidin B5, (+)-catechin, (-)-epicatechin, (+)-gallocatechin, (-)-epigallocatechin, β-amyrin, lupeol, 2,5-dimethylpyrazine, 3,5-dihydroxy-6-methyl-2,3-dihydropyran-4-one, indole, norharman, and methyl petroselinate were identified from these plants [ 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, HPLC analysis with standard flavonoids such as luteolin, kaempferol, and quercetin did not show any significantly identified levels of these compounds ( Figure 1 e), implying that major principles are not related to simple flavonoid backbones, and further phytochemical studies are needed. However, chemical analysis with Chrysophyllum plants such as C. lacourtianum, C. oliviforme, C. cainito , C. albidum, and C. pruniforme have been reported [ 37 , 38 , 39 , 40 ]. A variety of compounds, including 3-galloyl myrecetrin, rutin, quercetrin, myrecetrin, myricetin, quercetin, isoquercitrin, kaempferol, caffeic acid, trans-ferulic acid, gallic acid, stigmasterol, epicatechin, epigallocatechin, procyanidin B5, (+)-catechin, (-)-epicatechin, (+)-gallocatechin, (-)-epigallocatechin, β-amyrin, lupeol, 2,5-dimethylpyrazine, 3,5-dihydroxy-6-methyl-2,3-dihydropyran-4-one, indole, norharman, and methyl petroselinate were identified from these plants [ 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, chemical analysis with Chrysophyllum plants such as C. lacourtianum, C. oliviforme, C. cainito , C. albidum, and C. pruniforme have been reported [ 37 , 38 , 39 , 40 ]. A variety of compounds, including 3-galloyl myrecetrin, rutin, quercetrin, myrecetrin, myricetin, quercetin, isoquercitrin, kaempferol, caffeic acid, trans-ferulic acid, gallic acid, stigmasterol, epicatechin, epigallocatechin, procyanidin B5, (+)-catechin, (-)-epicatechin, (+)-gallocatechin, (-)-epigallocatechin, β-amyrin, lupeol, 2,5-dimethylpyrazine, 3,5-dihydroxy-6-methyl-2,3-dihydropyran-4-one, indole, norharman, and methyl petroselinate were identified from these plants [ 37 , 38 , 39 , 40 ]. Of them, interestingly, catechin and its analogs are known to be active principles showing antimelanogenic, anti-inflammatory, and antiwrinkle formation activities during UVB irradiation [ 41 , 42 , 43 ], although quercetin and its analogs are also known to be other major components with antiphotoprotective effects by radical scavenging activity [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many reports revealed that laser treatments of seeds at the appropriate time, power, and wavelength increased the number of morphological parameters such as root and shoot lengths and also increased crop yields and germination rates which was reported for fava bean and alfalfa (Perveen et al 2011). Plants have effective antioxidant compounds such as polyphenols and flavonoids (El-Hawary et al 2019); in addition, plants have an effective enzymatic antioxidant defense system including catalase (CAT), peroxidase, superoxide dismutase (SOD), and polyphenol oxidase enzymes. This system allows for scavenging of reactive oxygen species (ROS) leading to the protection of plant cells from oxidative damage (Caverzan et al 2016).…”
Section: Introductionmentioning
confidence: 97%
“…One of the main mechanisms involved in the development and pathogenesis of liver diseases is oxidative stress (Cichoż-Lach and Michalak 2014). Plant antioxidants can prevent hepatocellular injury by inhibiting the initiation or propagation of oxidative chain reactions and thus preventing the consequent cellular damage and homeostatic disruption (El-Hawary et al 2019). The use of natural antioxidants rather than synthetic drugs has risen as an alternative strategy to attenuate or prevent liver injury (Bursal et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The free radicals and reactive oxygen species (ROS) were highly reactive intermediates widely existing in human body, which can react with human biomolecules including lipids, proteins, DNA, etc, thus causing seriously detrimental health effects, such as neurodegenerative diseases, atherosclerosis, liver cirrhosis, cataracts, diabetes, and cancer ( Kang et al, 2007 ; López-Alarcónand Denicola, 2013 ). With the aim to clear up the oxidative stress resulting by excess amounts of ROS, numerous remarkable results have been reported in the past decades ( Cerutti, 1985 ; Halliwell, 1987 ; Breimer, 1990 ; Ding et al, 1999 ; Grisham et al, 2000 ; Aitken et al, 2012 ; Russell and Cotter, 2015 ; El-Hawary et al, 2019 ; Kusio et al, 2020 ). Among them, antioxidant was respected as one of the most efficient therapeutic strategies against human diseases related to oxidative damage by ROS ( Beckman et al, 1992 ; Taniguchi et al, 1993 ).…”
Section: Introductionmentioning
confidence: 99%